1922
DOI: 10.1017/s0021859600004494
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of winter wheat varieties with especial reference to winter-killing

Abstract: 1. A number of varieties of winter wheat, known to vary considerably in degree of winter hardiness, were compared in the hardened condition with reference to the physical constants of the cell sap, and the content of dry matter, nitrogen, sugars and starch.2. No constant relation was found between depression of the freezing point, specific conductivity, or hydrogen-ion concentration of the cell sap and relative frost hardiness.3. Sugars accounted for 34 to 38 per cent, of the total osmotic pressure of the sap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1926
1926
1955
1955

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…MAXIMOV (15) in his inivestigations came to the conclusion that the true measure of drought resistanee is the ability of the plant to survive exposure to drought without permanent injury. NEWTON (19,20) found that he eould distinguish cold-hardy from non-cold-hardy varieties of wheat on the basis of their bound water content. He also observed the higher sugar content of the hardy varieties as compared with that of the non-hardy, but assigned nio particular significance to it.…”
Section: Introductionmentioning
confidence: 99%
“…MAXIMOV (15) in his inivestigations came to the conclusion that the true measure of drought resistanee is the ability of the plant to survive exposure to drought without permanent injury. NEWTON (19,20) found that he eould distinguish cold-hardy from non-cold-hardy varieties of wheat on the basis of their bound water content. He also observed the higher sugar content of the hardy varieties as compared with that of the non-hardy, but assigned nio particular significance to it.…”
Section: Introductionmentioning
confidence: 99%
“…The latter factor was held to be insufficient to cause precipitation except under the conditions of a changed acidity. NEWTON (24), on the other hand, in an investigation of the hardiness of winter wheat, found no constant relation between the hydrogen-ion concentration, depression of the freezing point, or specific conductivity of the cell sap and relative frost hardiness. He also reported that the relation between water soluble nitrogen and hardiness was not constant.…”
Section: Historical Reviewmentioning
confidence: 97%
“…Among the more recent contributions on hardiness are two by NEWTON (24,25). Both of them deal with frost resistance in winter wheat.…”
Section: Historical Reviewmentioning
confidence: 99%
“…It has been noted that modifications of this winter hardiness factor can be brought about by subjecting the same plant to different environmental conditions. This is evidenced by the work of CHANDLER (1), ROSA (18), SALMON (20), and NEWTON (14). In view of these results it might be expected that plants of the same variety of wheat, but having attained different stages of seedling development would respond differently to freezing temperatures.…”
Section: Introductionmentioning
confidence: 94%